Huxley’s science fiction: ion channels in pain, pain resilience, and beyond - Waxman, Stephen (Henry Stewart Talks, 2025)
Osteoarthritis, Hodgkin-Huxley mechanism, Neuropathic pain, DRG neurons, Inherited erythromelalgia, Pain pharmacotherapy, Sodium channels, Pain genes and pain resilience genes, Genomic pain therapy